From leadership-as-practice to leaderful practice - Joseph A. Raelin (Leadership, 2011)
Consistent with views that see leadership emerging from social practices rather than from the external mind, this paper contributes to an emerging movement in leadership studies known as `leadership-as-practice' (L-A-P). This movement looks for leadership in its music and activity rather than in the traits and heroics of individual actors. The article distinguishes L-A-P from the individualistic approach by explaining its intersection with its dualistic counterpart, theory; with the agency—structure problem; and with relationality and meaning in organizations. It calls for a modification in classic approaches to research methodology and to leadership development. L-A-P is advised to consider its natural affinity with democratic participation through leaderful practices that systematically privilege the co-creation of social organization.
Keywords: J24; M10; M12; M14; M53; O15; 330; Leadership; Leadership-as-practice; Leaderful practice; Agency vs. Structure; Collective leadership; Distributed leadership; Leadership development